MINERAL PROFILING OF CHILLI PEPPER (CAPSICUM ANNUUM L.) INOCULATED WITH COLLETOTRICHUM CAPSICI (SYDOW), BUTLER AND BISBY - M. Bashair; N. Javed; M. Atiq; W. Wakil (Journal of Animal and Plant Sciences, 2016)
Chilli pepper is among the world’s most popular vegetable crop with a ranking of third after potato and tomato. Anthracnose caused by Colletotrichumcapsici can cause large losses to chilli. Experiments were done to determine if the mineral status of chilli is affected by infection with the anthracnose pathogen. Fruits of resistant and susceptible cultivars of inoculated and un-inoculated chilli pepper plants from six varieties/lines were collected in 2013 and 2014 and tested using nested design to determine their mineral/nutrient composition. There was variation (p ≤ 5) in the mineral status among treatments group (inoculated & un-inoculated), type (resistant & susceptible) and in varieties/lines of the chilli plants due to the infection by anthracnose disease. Resistant type of plants expressed 2.81, 2.52, 2259,1185.50, 64.95, 179.60, 431.63, 141.12, and 110.58 while susceptible type showed 1.88, 1.66, 2562.67, 991.48, 35.40, 121.28, 140.87, 191.83,and 137.04 variation in concentration of nitrogen (N), phosphorous (P) (%), while potassium (K), calcium (Ca), magnesium (Mg), zinc (Zn), sodium (Na), iron (Fe), and copper (Cu) in ppm respectively. Resistant cultivars accumulated higher concentrations of these minerals compared to susceptible varieties and this increase in minerals in resistant host plants could help prevent the spread of pathogen by strengthening the biochemical and physiological processes of the host.
Keywords: Capsicum annuum; Colletotrichumcapsici; minerals; nested design; Solanaceae